Association between physical measures of spinopelvic alignment and physical functioning with patient reported outcome measures after total hip arthroplasty: Systematic review and narrative synthesis - Sima Vatandoost; Saghar Soltanabadi; Renee-Marie Ragguett; Lucas Fernandino; Brent Lanting; K.C. Geoffrey Ng; Katie Kowalski; Alison Rushton (PLoS ONE, 2025)
Background The prevalence of total hip arthroplasty (THA) is increasing, making optimizing post-surgery outcomes essential. Co-occurrence of low back pain (LBP) is frequently reported. Patient-reported outcome measures (PROMs) are commonly used to evaluate outcomes but have limitations, and physical measures may have value. This study evaluated association between 1] physical measures of spinopelvic alignment (measuring from spine to the pelvis) and physical functioning with PROMs after THA, and 2] physical measures with LBP. Methods Systematic review (PROSPERO: CRD42023412744) searched electronic databases, grey literature, and key journals to 31/5/2024 for cross-sectional and longitudinal studies assessing associations following THA. Two independent reviewers evaluated eligibility, extracted data, and assessed risk of bias (RoB, NIH tool). Owing to heterogeneity, a narrative synthesis was conducted, and GRADE determined overall quality. Results Fifty-one studies were included: 8 low-RoB, 24 moderate-RoB, 19 high-RoB. The evidence on spinopelvic alignment was extremely limited (6 studies), with the main synthesis focusing predominantly on physical measures of physical functioning. Very low-quality evidence supports no cross-sectional association between walking speed with function in short-term, and between light-intensity physical activity with patient-reported physical activity in medium-term. Very low-quality evidence supports no longitudinal association between Timed-Up-and-Go change with pain/function change, and Stair-Climb-Test (SCT) change with pain/function change in short-term, and SCT change with function change in medium-term. Other findings were inconsistent. Three LBP studies could not be synthesized due to heterogeneity. Conclusions Very low-quality evidence supports no association between physical measures of physical functioning with PROMs, with limited LBP studies. There was significant heterogeneity, with few low ROB studies, highlighting a need for future research on the association between the measures.